Distress disorder histories predict HRV trajectories during and after stress. (January 2022) - Renna, Megan E.; Shrout, M. Rosie; Madison, Annelise A.; Bennett, Jeanette M.; Malarkey, William B.; Emery, Charles F.; Kiecolt-Glaser, Janice K.
Abstract: Background: Breast cancer survivors face a number of physical health threats including cardiovascular disease, the leading cause of death among breast cancer survivors. Low heart rate variability (HRV) represents one well-established risk factor for poor cardiovascular health. Among physically healthy adults and breast cancer survivors, distress disorders may contribute to lower HRV, enhancing morbidity and mortality. This study examined how a distress disorder history altered survivors' HRV trajectories during and after an experimental stressor. Methods: Breast cancer survivors ( n = 178; mean age = 51.22) who finished treatment for stages 0-IIIa cancer within the past two years completed a diagnostic interview assessing lifetime presence of psychological disorders. They also participated in a Trier Social Stress Test (TSST). HRV data provided information on survivors' cardiovascular responses at baseline, during the TSST, and during recovery. HRV recovery data at 45 min and 120 min post-TSST was also collected. Survivors also completed questionnaires before and after the TSST assessing task performance, stress levels, ability to cope, and hopelessness. Covariates included body mass index, age, cancer stage, cardiovascular medications, exercise, menopause status, fatigue, current depressive and anxiety symptoms, and physical comorbidities. Results: Women with a distress disorder history had significantly lower HRV before, during, and after the TSST compared to women without such a history. Survivors with distress disorders found the TSST to be more threatening, and reported feeling less control over their performance than those without distress disorders. Conclusions: Breast cancer survivors with a distress disorder history may have lower autonomic flexibility before, during, and after stress exposure. Distress disorder histories also heighten several stress-related risk perceptions leading up to and following the TSST. These findings highlight distress disorder histories as a unique correlate of poorer cardiovascular function among survivors. Highlights: Low HRV is a risk factor for cardiovascular disease. Breast cancer survivors had HRV measured before, during, and after the TSST. Survivors completed an interview to assess current and past distress disorders. Distress disorder histories corresponded to lower HRV throughout the stressor. Distress histories may therefore enhance cardiovascular disease risk for survivors.